2018
DOI: 10.1002/jmri.26240
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Prediction of IDH1 Mutation and ATRX Expression Loss in Low‐Grade Gliomas Using Multiparametric MR Radiomic Features

Abstract: 3 Technical Efficacy Stage: 2 J. MAGN. RESON. IMAGING 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 37 publications
4
50
0
Order By: Relevance
“…Our findings confirm the results of former investigations highlighting the impact of texture analysis on disease characterization . As a strength of our study, we assessed changes in texture features over a period of time .…”
Section: Discussionsupporting
confidence: 91%
“…Our findings confirm the results of former investigations highlighting the impact of texture analysis on disease characterization . As a strength of our study, we assessed changes in texture features over a period of time .…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, we were also able to show which image features were important in the classification, increasing the clinical understand-ing of the machine learning algorithm and potentially aiding better acceptance, as well as furthering fundamental research into understanding of glioma pathophysiology. Although other studies did already investigate the noninvasive prediction of the molecular subtype of LGG, these often focused on IDH mutations only and did not consider the 1p/19q codeletion status (11,28,29). In comparison with studies that did look at the 1p/19q codeletion, we used a larger cohort and an external validation dataset (10,13,14,30,31), which makes our results more robust and generalizable, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…To break through the limitations of the conventional analysis methods, this study proposed a combined analysis of ROI‐based features at all cervical levels. Such ROI‐based features can provide more details of the inside of the spinal cord, and have been demonstrated to be more effective than whole‐cord‐based features for describing the status of the spinal cord . In this study, the ROI drawing was performed by experienced neuroimage researchers with a well‐established ROI drawing method; however, a question may still be raised concerning the accuracy of the ROI drawing in the seriously compressed cervical spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Besides whole‐cord‐based features, DTI features can be extracted from the DTI metric maps via the drawing of a region of interest (ROI) inside the spinal cord. These ROI‐based features can provide detailed information on the tissues inside the spinal cord, and their feasibility and effectiveness for describing the spinal cord has previously been shown in several studies . In addition, it has been demonstrated that cervical levels other than the MCCL also contain information that is useful for the prognostic process, and thus DTI features at these cervical levels may also be of benefit for the prognosis.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation